The War of Time: Occupation, Resistance, Communization - Noys, Benjamin (Identities: Journal for Politics, Gender and Culture, 2013)
Contemporary theorizations of strategies of resistance and revolution often turn on affirming the concepts of speed and saturation. I want to critically consider these claims by returning to the work of Paul Virilio from the 1970s and contemporary “communization theory.” These theorizations stress the emptying-out of traditional worker’s identity and the need to re-invent forms of resistance and revolution that can address this challenge. My aim is to assess how both engage with the problem of acceleration, and particularly the relation of resistance to forms of contemporary military power. I will argue that strategies of acceleration find themselves in fraught convergence with both military and capitalist practice. Author(s): Benjamin Noys Title (English): The War of Time: Occupation, Resistance, Communization Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 83-92 Page Count: 10 Citation (English): Benjamin Noys, “The War of Time: Occupation, Resistance, Communization,” Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013): 83-92.